2017
DOI: 10.12816/0040629
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Mothers on Acute Respiratory Infection in Children under Five Years in Saudi Arabia, 2017

Abstract: Background: management and prevention of acute respiratory infections (ARI) is a worldwide problem especially in developing countries. Mothers are the caregivers of their children and thus their knowledge could be used as preventive measure for the disease. Objectives: assessing the knowledge, attitude and practice (KAP) of Saudi mothers toward ARI in children less than five years old in the Kingdom of Saudi Arabia. Methods: the study included 733 mothers admitted to a random sample of PHC from different distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…This was in contrast with findings by other researchers. [1121] Knowledge of symptoms of ARI was very good among caregivers (98%), which was higher than other studies. [22] Use of self-medication was found (43.6%) in this study which is similar to other studies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This was in contrast with findings by other researchers. [1121] Knowledge of symptoms of ARI was very good among caregivers (98%), which was higher than other studies. [22] Use of self-medication was found (43.6%) in this study which is similar to other studies.…”
Section: Discussionmentioning
confidence: 84%
“…This was slightly higher than other studies. [11242526] 66.3% of parents showed a healthy practice of minimizing indoor air pollution. 89.1% parents agreed that they visit a physician whenever child presents with symptoms such as cough, fever, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age and knowledge/ perceptions relationship is varied. (28,54) Higher education is almost universally associated with better knowledge /perception, (28,54,55) hence promoted. (56) We observed that although knowledge was proportional to education, perception was not.…”
Section: Associations Between Different Variablesmentioning
confidence: 99%
“…(27)(28) Knowledge about signs and symptoms among mothers varies from poor to adequate. (1,17,24,(30)(31)36,54) Despite affirming knowing pneumonia, only 24.4% women could describe pneumonia using closest word 'severe cold'. (29) More than 80% mothers in Peru know that chest in-drawing and rapid breathing are signs of pneumonia.…”
Section: Knowledge and Perception About Pneumoniamentioning
confidence: 99%